Protest Against Child Exploitation: A Sociological Study on Charles Dickens' Oliver Twist - Sahistya Hadi, Agung, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
This article deals with the close relation between literature and the social realities where the literary work was produced. The study aims at finding the relation between Oliver Twist and the social realities of the English society in the first half of the nineteenth century. The primary source of data was the novel itself, and the secondary source data includes documents related to the topic. The main findings of the study are as follows: (1) the industrialization strengthened the domination the middle class to the lower class and this condition was close to exploitation; (2) the New Poor Law of 1834 and the Factory Act of 1833 could not prevent the children from exploitation; (3) the types of exploitation were physical, psychological, economic, political, and situational exploitation. The study concluded that the novel represented Dickens' criticism against the child exploitation that occurred in the English society at the first half of the nineteenth century.